Essential vs. Desired Digital Skills in Hotel Industry - Yudistira, Sukma (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
This study aims to identify and analyze the digital skills required in the hotel industry and distinguish between those necessary for basic operations and those desired for enhanced performance and competitive advantage. By reviewing the existing literature, this study provides a comprehensive overview of the digital competencies’ hotel employees need to acquire to thrive in a digitalized environment. Furthermore, this study offers insights into which digital skills should be considered of high precedence and which are of lower precedence for inclusion in hotel management programs. The findings of this research have significant implications for both hotel management and education programs, particularly in terms of arranging effective training programs. By identifying critical and desirable digital skills, hotel management programs can design more targeted and relevant curricula that better prepare students for the demands of the industry. Additionally, the results can serve as a reference for hotel development plans, ensuring that both current and future employees possess the digital competencies necessary to excel in their roles.